Estudo da relação entre proteína B-amilóide, neuroregeneração e deficiência cognitiva após hipoperfusão cerebral crônica e progressiva : efeitos do sildenafil - Ferreira, Emilene Dias Fiuza (2010)
This study is a continuity of previous works performed in our laboratory with the aim of developing an animal model of chronic cerebral hypoperfusion (HCC). The development of animal models that reproduce a condition of cerebro- vascular insufficiency is essential to study the pathophysiology of neurodegenerative diseases associated with a state of HCC, as well as for developing therapeutic strategies. In previous studies we reported that permanent 4-VO/ICA, with an interval of 7 days between each occlusion stage ('interstage interval', ISI), and chronicity of up to 60 days, was unable to cause both cognitive dysfunction and brain neurodegeneration. Permanent 4-VO/ICA has the advantage, however, of preserving the histomorphological integrity of the retina, which lesion may influence negatively the results of behavioral analysis (Barros et al., 2009). In this study we aimed to investigate, primarily, whether 4-VO/ICA could be effective to cause concomitant learning/memory dysfunction and neurodegeneration in young rats if the ISI would be reduced (from 7 to 5, 4, 3 or 2 days) and the chronicity would be prolonged (from 60 to 90 days). Also, whether 4-VO/ICA could change the expression of the amyloid precursor protein (APP) was investigated. Given the negative results observed in the young rat, in a second experiment we investigated whether middle-aged rats could undergo both cognitive disruption and neuropathological changes after permanent, 3-stage 4-VO/ICA with similar conditions of ISI and chronicity. Moreover, in a post-hoc analysis we evaluated whether 4-VO/ICA-induced neurodegeneration could extend beyond the hippocampus. Finally, in a subsequent experiment the effects of sildenafil (Viagra®) could alleviate the cognitive and neurodegenerative effects of 4-VO/ICA in aged rats. Young (3 months) or middle-aged (15 months), male Wistar rats were used. Permanent 4-VO/ICA was induced by simultaneous, bilateral electrocoagulation of the vertebral arteries (VA) followed by stepwise ligation of the internal carotid arteries (ICA) according to the sequence VA-ICA-ICA, with an ISI- of 5, 4, 3 or 2 days. Ninety days after the last stage of occlusion (or shamoperation), the performance of learning and memory was measured in the eight arm, aversive radial maze, over 15 consecutive days, and expressed by the following parameters: (i) latency to find the goal box, (ii) number of reference memory errors, and (iii) number of working memory errors. Sildenafil (3.0 mg/kg) was given orally for 9 days, starting on the first occlusion stage (2-VO, vertebral arteries). At the end of behavioral testing, brains were examined for hippocampal and cortical neurodegeneration (celestine blue/fucsin acid staining), and expression of the amyloid protein precursor (APP). Permanent, 3-stage 4-VO/ICA did not affect the learning /memory performance of young rats, independently of the ISI (5, 4, 3 or 2 days) (Between Group effect, p > 0,05). A highly significant training effect was, however, observed for all groups (Within Group effect, p < 0.0001), indicating that the groups learned the task with similar rate. This behavioral performance of young rats occurred in spite of marked neuronal loss in the hippocampus (p <0.0001 vs. Sham). In young rats, there was no significant lesion in the cerebral cortex (p > 0,05 vs. sham). Qualitatively, an apparent, increase dimmunopositivity for (APP) was observed in the thalamus, after 4-VO/ACI in young rats. Unlike young rats, aged rats underwent learning disruption after permanent 4-VO/ICA with an ISI of 4 days (p < 0.0001 - 0.001). In these animals, marked neurodegeneration was present in both hippocampus (54%, p < 0.0001) and cerebral cortex (47%, p < 0.0001) and the treatment with sildenafil (3,0 mg/kg) protect at the hippocampal and cortical neurodegeneration after 4-VO/ICA (p<0.0001). An apparent, mild immunorreactivity for (APP) was also observed in aged animals. Sildenafil treatment (3.0 mg/kg, p.o.) did not reduce the learning deficit induced by 4-VO/ICA in aged rats. The present data suggest that permanent, 3-stage 4-VO/ICA can not be a suitable animal model of CCH in young rats, if maze-guided cognitive functions, such as spatial learning and memory, are to be measured. On the other hand, the 4-VO/ICA model may represent a useful paradigm to study the relationship between CCH-induced cognitive impairments and neurodegeneration, with the advantage of not causing retinal damage. Importantly, the present data suggest that the occurrence of neurodegeneration in the cerebral cortex of old, but not young rats after 4-VO/ICA, could explain the different behavioral response observed among those groups. Finally, the treatment with sildenafil fails to alleviate the 4-VO/ICA-induced learning deficit in aged rat. Sildenafil treatment (3,0 mg/kg) was able to reduce the neurodegeneration at the hippocampus and cerebral cortex when submitted 4-VO/ICA.